A Week in the Life: Pediatric Palliative Care through the Eyes of a Medical Student - Eileen Williams; Jill Ann Jarrell; Jared Rubenstein (MDPI AG, 2021)
To complete the curriculum, learners rotating through a pediatric palliative care service are asked to submit a piece of reflective writing. Here, we share an edited version of the narrative one student submitted, accompanied by a brief consideration of the numerous benefits of reflective writing for medical trainees (including improved communication and professionalism skills, as well as increased levels of empathy and comfort when facing complex or difficult situations). Additionally, we describe how brief personal narratives may serve to reduce common misconceptions and confusion by educating patients, families, and clinicians about the reality and the role of pediatric palliative care.